1993
DOI: 10.2307/3431488
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Carcinogen-DNA Adducts in Human Fetal Tissues by the 32 P-Postlabeling Procedure

Abstract: Tobacco smoke contains a number of genotoxic compounds that are metabolized to their biologically active forms that subsequently react with cellular DNA to form covalently boundcarcinogen-DNA adducts. Several analytical procedures have been developed to detect these adducts in human tissues. Using the nuclease P1-enhanced 32P-postlabeling procedure for bulky adducts, we have detected at least 24 adducts in DNA isolated from placenta and umbilical cord DNA. Adducts were detected in both smokers and nonsmokers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Exposure of pregnant rats to BaP via oral or inhalation routes results in BaP-dosedependent concentrations of BaP metabolites in blood and tissues of offspring on the day of birth, with levels declining over the subsequent postnatal weeks (Wu et al 2003;Jules et al 2012). Smoking-related DNA and albumin adducts, including BaP-specific adducts, have been detected in human fetal tissues (Hansen et al 1993;Autrup and Vestergaard 1996). Humans are exposed to dozens of mutagenic PAHs in addition to BaP.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of pregnant rats to BaP via oral or inhalation routes results in BaP-dosedependent concentrations of BaP metabolites in blood and tissues of offspring on the day of birth, with levels declining over the subsequent postnatal weeks (Wu et al 2003;Jules et al 2012). Smoking-related DNA and albumin adducts, including BaP-specific adducts, have been detected in human fetal tissues (Hansen et al 1993;Autrup and Vestergaard 1996). Humans are exposed to dozens of mutagenic PAHs in addition to BaP.…”
Section: Discussionmentioning
confidence: 99%
“…There are a growing number of studies that show a relationship between DNA adduct levels in placenta, exposure to environmental PAHs or tobacco smoke, and activity of cytochrome p450s [Everson et al, 1986[Everson et al, , 1987Hansen et al, 1993;Topinka et al, 1997;Whyatt et al, 1998a,b;Lagueux et al, 1999]. One possibility is that the control subjects who provided placenta 12 months after the oil fires were exposed to PAHs other than through airborne pollution, which might include sources such as contamination of food or drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the presence of smoking-related DNA adducts in placenta [Everson et al, 1986, Hansen et al, 1993Topinka et al, 1997] and elevations of DNA adducts associated with smoking have been reported for a variety of tissues, including lung, kidney, bladder, esophagus, and oral tissues [Phillips et al, 1988b;Randerath et al, 1989;Cuzick et al, 1990;Jones et al, 1993]. As expected, adduct levels were found to be lower in the placental samples from nonsmoking mothers, in which the mean values were roughly half those seen in smoking mothers for both enhancement techniques (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations